2005
DOI: 10.1021/ie050398d
|View full text |Cite
|
Sign up to set email alerts
|

SCR of NO by Propene on Monometallic (Co or Ni) and Bimetallic (Co/Ag or Ni/Ag) Mordenite-Based Catalysts

Abstract: Selective catalytic reduction of NO by propene was investigated on monometallic (Co or Ni) and bimetallic (Co/Ag or Ni/Ag) mordenite-based catalysts in the presence of an oxygen excess. Results showed that the catalytic activity of monometallic catalysts prepared from the zeolite sodium form was higher than that for the catalysts prepared from the sodium form. Opposite performances were found for the bimetallic (Co/Ag or Ni/Ag) catalysts. These results were related to both the location and stability of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 61 publications
1
21
1
Order By: Relevance
“…This is attributed to the formation of a secondary lattice generated by occupation of the zeolite cages by Ag(I) ions. Previous Al MAS NMR studies [27] have suggested that the distribution of framework Al atoms in zeolites is organized and not random [30]. A phenomenon very similar to that seen in the XRD spectra of the Y zeolitebased catalysts can be seen for the XRD spectra of the synthesized sodalite and the Fe-SOD, Ag-SOD, and Ag/Fe-SOD catalysts.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This is attributed to the formation of a secondary lattice generated by occupation of the zeolite cages by Ag(I) ions. Previous Al MAS NMR studies [27] have suggested that the distribution of framework Al atoms in zeolites is organized and not random [30]. A phenomenon very similar to that seen in the XRD spectra of the Y zeolitebased catalysts can be seen for the XRD spectra of the synthesized sodalite and the Fe-SOD, Ag-SOD, and Ag/Fe-SOD catalysts.…”
Section: Resultssupporting
confidence: 66%
“…Previous research has found that introduction of a second metal ion to the Ag(I) clusters results in enhancement of catalytic activity [21][22][23][24][25][26][27]. Research specific to decontamination purposes has found that decomposition of the nerve agent simulant dimethyl methylphosphonothioate (DMMP), which has a functional group similar to carbaryl, is enhanced by the participation of an Fe(III)/Fe(II) mixedvalence couple [28].…”
Section: Introductionmentioning
confidence: 99%
“…9 shows new bands in the 2300-2050 cm −1 region, which correspond to intermediate species produced by the reaction between the adsorbed toluene and NO at 400 • C. The band at 2266 cm −1 is usually assigned to the stretching vibration of isocyanate groups (N=C=O) on Ag + ions while the signals at 2130 and 2100 cm −1 are assigned to cyanide (Ag-CN) and isocyanide (Ag-NC) species adsorbed on the catalyst surface, respectively (Dorado et al 2005;Yeom et al 2007;Shimizu et al 2001;Tamm et al 2008;Thibault-Starzyk et al 2009). …”
Section: Toluene Adsorption Followed By Sweep With 1000 Ppm No/he Flowmentioning
confidence: 99%
“…However, it seems that only limited types of zeolites including ZSM-5 (Li et al, 2004;Li et al, 2008;Wang et al, 2007a;Wang et al, 2007b;Wang et al, 2005;Niu et al, 2006), ferrierite (Seijger et al, 2003;Lee et al, 2003;Kubacka et al, 2005;Kubacka et al, 2006) and mordenite (Pieterse & Booneveld, 2007;Mosqueda-Jiménez et al, 2003a;Córdoba et al, 2005;Lónyi et al, 2007;Dorado et al, 2005), which are called as pentasil zeolites, displayed high selectivity to NO x reduction in HC-SCR. For instance, Pieterse et al (Pieterse et al, 2003) investigated the selective catalytic reduction of NO by methane (CH 4 -SCR) over several zeolite-based catalysts and reported an activity order of Co-Pd-ZSM-5 > Co-Pd-MOR > Co-Pd-FER > Co-Pd-BEA.…”
Section: To Characterize Surface Acidity Of the Catalystmentioning
confidence: 99%